Resilient food systems and sustainable agri value chains, high level panel meeting - (:unkn) unknown (My University, 2023)
The presentations and panel discussions aim at:1. Exploring how existing AU-EU cooperation platforms may be supported and upscaled to set up a well-functioning, long-lasting AU-EU Agricultural Knowledge andInnovation System fostering smart policies, capacities strengthening, reduction inknowledge gaps and innovative technologies.2. Gathering policy guidance and expert advice as regards future R&I activities reflecting the importance of Soil Health for African agri-food systems, rural populations and climate.3. Identifying which smart policies and technologies, and data-driven digitalsolutions, can best contribute to enabling policies, fostering innovation and valorisingdigitalisation, considering the need to adopt a systems approach to address the complexity of the green transition in both Africa and Europe.4. Highlighting the most prominent AU-EU relevant policy initiatives, in particular the (newly adopted by then) AU-EU Innovation Agenda and the AU draft DigitalTransformation Strategy for Agriculture, developed with EU support in the contextof PRIDA and to be adopted at the AU Specialised Technical Committee scheduled in late 2023
Keywords: African Research